First report of a dead giant squid (Architeuthis dux) from an operating seismic vessel. Issue 1 (December 2016) - Leite, Luciana; Campbell, Daniel; Versiani, Leonardo; Nunes, José; Thiele, Torsten
Abstract We report the first sighting of a dead giant squid observed from a seismic vessel operating offshore Brazil. The observation was made by Marine Mammal Observers working on the vessel. The specimen was photographed and identified asArchiteuthis dux on the basis of its size and morphology. Our report adds to the limited data regarding the distribution of this species in the Southern Atlantic Ocean. Because the animal was not examined, its death cannot be conclusively linked to the seismic activity. Nevertheless, given the scarcity of observations of this species offshore Brazil, we believe this record helps to understand the species distribution as well as to highlight the disturbing lack of information on the impacts of marine sound pollution on invertebrates. This record also serves as another call for further research and for the use of precautionary principle to protect species in the deep sea.